Fundamental approaches to software engineering : 15th International Conference, FASE 2012, held as part of the European joint conferences on theory and practice of software, ETAPS 2012, Tallinn, Estonia, March 24 - April 1, 2012. Proceedings - Zisman, Andrea; Lara, Juan (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 15th International Conference on Fundamental Approaches to Software Engineering, FASE 2012, held in Tallinn, Estonia, in March/April 2012, as part of ETAPS 2012, the European Joint Conferences on Theory and Practice of Software. The 33 full papers presented together with one full length invited talk were carefully reviewed and slected from 134 submissions. The papers are organized in topical sections on software architecture and components, services, verification and monitoring, intermodelling and model transformations, modelling and adaptation, product lines and feature-oriented programming, development process, verification and synthesis, testing and maintenance, and slicing and refactoring.